The Impact of the Management and Improvement on Engagement and Satisfaction of Employees in the Public Institution in the Sphere of Culture (Journal of Universal Excellence, 2026)
Research question (RQ): What ist the relationship between management and improvement, engagement and job satisfaction of employees?Purpose: This study aims at investigating the relationship between management and improvement, engagement and job satisfaction of employees. We also try to find out which factors have the greatest or most powerful influence on management and improvement, employee engagement and job satisfaction.Method: To determine the level between management and improvement, engagement and satisfaction of employees we used the quantitative method respectively surveys. The data was analysed with PLSM-PL (Partial Least Squares Path Modeling) method using the statistical package R and function plspm. Based on this method we investigate multi variant relatinoships between observed and latent variables.Results: The results confirmed that management and improvement have a strong direct effect on the satisfaction (0,745) and employee engagement (0,600). The most powerful factors that influenced engagement and satisfaction are connected with leadership.Organisation: Survey results offer the management the basis to improve resources management. Engagement and satisfaction of employees in connection with the leadership offer a big development potential for organisations in the public sector.Originality: The original contribution can be seen in the study of the cause and effect relationship of the engagement and satisfaction of employees. The majority of such surveys focuses either on the study of engagement and satisfaction in connection with other factors or on their relation to demographic data.Limitations / further research: The fact that this is the first study of its kind in the institution under discussion represents a sizeable constraint, especially in an institution where the leadership has not yet begun to introduce the principles of quality management (TQM).
Keywords: public sector; engagement; job satisfaction; quality